(untitled) (Ágora UNLaR, 2025)
This article analyzes the development and evolution of dynamic capabilities, focusing on cur-rent trends in their study and application within organizations. Dynamic capabilities have gained significant attention in recent years due to their relationship with innovation, adaptation, and organizational resilience. However, organizations face barriers to their effective implementation, such as resistance to change, lack of technological integration, and ineffective knowledge management. Key trends include digitalization, technological transformation, and sustainability, which are reshaping how dynamic capabilities are developed. The article aims to provide a comprehensive overview of these capabilities, identifying emerging trends and persistent obstacles. It addresses two main research questions: What are the current trends in the study of dynamic capabilities? And what barriers limit their implementation in organizations? his approach highlights the im-portance of the topic, emphasizing trends and framing the questions that guide the analysis.